Performance of Protective Clothing: Fourth Volume 1992
DOI: 10.1520/stp19192s
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ventilation of Firefighter Protective Clothing

Abstract: Wearing protective garments under various combinations of environmental conditions and work intensities may result in excessive heat stress. Maintaining thermal balance depends among others on the ventilation of the garment worn. Ventilation is the amount of ambient air that flows under the garment after passing through the fabric and through designed openings. A gas dilution technique was used to assess ventilation of firefighter protective ensemble. The cuffs of the sleeves and pants, and the collar and fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…The absence of statistical significance is likely to be partly attributable to Textile Progress too few observations as only two participants were included in the trial. In a similar study, the collar and front closures of fire fighters' protective gear were shown to have the greatest effect on ventilation when the garments were tested on a human manikin [372]. Other parts of the garment investigated as 'opened' and 'closed' were cuffs of the sleeves and pants, and the waistline, the latter achieved using either braces or a belt.…”
Section: Ventilation and J'entsmentioning
confidence: 93%
See 2 more Smart Citations
“…The absence of statistical significance is likely to be partly attributable to Textile Progress too few observations as only two participants were included in the trial. In a similar study, the collar and front closures of fire fighters' protective gear were shown to have the greatest effect on ventilation when the garments were tested on a human manikin [372]. Other parts of the garment investigated as 'opened' and 'closed' were cuffs of the sleeves and pants, and the waistline, the latter achieved using either braces or a belt.…”
Section: Ventilation and J'entsmentioning
confidence: 93%
“…(Ventilation has also been in\estigated using other laboratory methods such as human manikins (e.g. [372]) and cyhnders (e.g. [373]).…”
Section: Ventilation and J'entsmentioning
confidence: 99%
See 1 more Smart Citation
“…For workers who operate in warm environments or who perform heavy physical activity, heat strain may occur as a result of the personal protective clothing being worn. 4 For firefighters, thermal protection is of utmost importance; however, a contradiction occurs between the necessary thermal protection required and the need for heat loss. 1 Heat loss through protective clothing…”
Section: Heat Strain In Protective Clothingmentioning
confidence: 99%
“…4,5 When the body performs physical activity it produces heat which must escape from the body in order to maintain a balanced core temperature. If this heat cannot escape, heat strain, fatigue, stroke, and even death may occur for the wearer.…”
Section: Heat Strain In Protective Clothingmentioning
confidence: 99%